BASIC COMPONENTS OF MICRO TEACHING SKILL AT THIRD YEAR STUDENTS FKIP UNIVERSITAS PASIR PENGARAIAN - Welven Aida; Rivi Antoni (JEE (Journal of English Education), 2017)
The basic components of micro teaching skill is the basic skill to students who are going to be a teacher. Micro teaching is a course to practice teaching in faculty of teacher training and education.The research was done at third years students in 4 Department of FKIP in Universitas pasir pengaraian ( English Study Program, Math, Physic and Biology) .The methodology of this research is qualitative research. The researcher uses the teacher instrumentation assessments (IPKG 2). From the analysis, it can be concluded that the basic components of micro teaching skill at third years students of FKIP in Universitas Pasir Pengaraian is in good category or in 68,75%.